Management of Late-Onset Complete Atrioventricular Block Post Transcatheter Closure of Perimembranous Ventricular Septal Defects - Xie, Lijian; Zhang, Han; Zhang, Rufang; Xiao, Tingting (Frontiers in Pediatrics, 2020)
Background: Long-term late-onset complete atrioventricular block (CAVB) is one of the most serious complications of transcatheter closure of perimembranous ventricular septal defect (pmVSD), which can cause Adams_Stoke attack, even sudden death. Transcatheter closure of pmVSD is not approved by FDA, yet the procedure has been a successful alternative to surgical strategy in China. Although transcatheter closure of pmVSD is widely and successfully performed in the world especially China, late-onset CAVB is still difficult to avoid. Here we reported a case with late-onset CAVB post transcatheter closure that was successfully treated. By doing so, we reassess the safety of pmVSD occluder closure, and this procedure should adhere to more stringent indication.